Determination of the interfacial strength and fracture toughness of a-C:H coatings by in-situ microcantilever bending - Schaufler, Jens; Schmid, Christoph; Durst, Karsten; Göken, Mathias (Thin Solid Films, 2012)
The interfacial fracture strength and toughness of two hydrogenated amorphous carbon coatings (a-C:H) with Cr-adhesion layers on steel substrate have been determined directly by in-situ deformation tests using microcantilever bending experiments. The coating conditions for the two systems were essentially the same, only slight differences have been introduced in the adhesion layer. These changes resulted in a totally different delamination behavior, from excellent to poor adhesion. The well adherent interface between the adhesion layer and the a-C:H has a fracture strength and toughness value close to the a-C:H coating itself. For bulk a-C:H a bending strength close to the theoretical strength was found, indicating that the tested volume was defect free. Changing the process conditions reduced the bending strength by 40%, leading to strong delamination and a catastrophic behavior during Rockwell C testing. An interfacial fracture toughness value of 2.18 MPa m0.5 was found for the well adherent coating, exceeding even that of pure a-C:H.
WW1::921